Quantum Chromodynamics at High Energy - Kovchegov, Yuri V. (Cambridge University Press, 2013)
Filling a gap in the current literature, this book is dedicated to high energy quantum chromodynamics (QCD) including parton saturation and the color glass condensate (CGC). It presents groundbreaking progress on the subject and describes many problems at the forefront of research, bringing postgraduate students, theorists and interested experimentalists up to date with research in this field. The material is presented in a pedagogical way, with numerous examples and exercises. Discussion ranges from the quasi-classical McLerran-Venugopalan model to the linear BFKL and nonlinear BK/JIMWLK small-x evolution equations. The authors adopt both a theoretical and an experimental outlook, and present the physics of strong interactions in a universal way, making it useful for physicists from across high energy and nuclear physics, and applicable to processes studied at high energy accelerators around the world. This title, first published in 2013, has been reissued as an Open Access publication on Cambridge Core.